Uji Toksisitas Ekstrak Etanol Kulit Terong Ungu (Solanum melongena L.) Menggunakan Metode Brine Shrimp Lethality Test (BSLT) - Nur Rahma Dwi Cahya; Widy Susanti Abdulkadir; Hamsidar Hasan (State University of Gorontalo, 2022)
Purple eggplant skin (Solanum melongena L.) is one of the herbal plants that contain compounds such as flavonoids, alkaloids, saponnins, tannins, and terpenoids that are beneficial for health. This research is a laboratory experimental study that aims to determine the level of acute toxicity (LC50) of the ethanol extract of purple eggplant skin (Solanum melongena L.) using the Brine Shrimp Lethality Test (BSLT) method. Purple eggplant peel extraction was carried out using 70% ethanol as solvent. This test was conducted using 10 Artemia salina Leach larvae with 3 replications at 6 concentration variants, which are 500 ppm, 250 ppm, 125 ppm, 50 ppm, 25 ppm, and 12.5 ppm, along with negative controls. The larval mortality rate was observed after 24 hours of adding extract. The result of probit analysis showed that the LC50 value of the ethanol extract of purple eggplant skin (Solanum melongena L.) was 100.8 ppm. Moreover, the results of LC50 1000 ppm indicated that the ethanol extract of purple eggplant skin (Solanum melongena L.) was considered toxic and potential to be an anticancer agent.